Determinants of banks' engagement in loan securitization - Christina E. Bannier; Dennis N. Hänsel (Frankfurt School of Finance & Management, 2007)
This paper provides new insights into the use of loan securitization. We analyze collateralized loan obligation (CLO) transactions by European banks from 1997 to 2004 and try to identify the influence that various firm-specific and macroeconomic factors may have on an institution's securitization decision. Our results suggest that loan securitization is an appropriate funding tool for banks with high risk and low liquidity. It may also have been used by commercial banks to indirectly access investment-bank activities and the associated gains. Regulatory capital arbitrage under Basel I does not seem to have driven the market.
urn:nbn:de:101:1-20080827350
Keywords: G21; 330; Securitization; credit risk transfer; collateralized loan obligations